2009
DOI: 10.1007/s00421-009-1195-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning improves maximal performance in humans

Abstract: Repeated episodes of ischemia followed by reperfusion, commonly referred to as ischemic preconditioning (IPC), represent an endogenous protective mechanism that delays cell injury. IPC also increases blood Xow and improves endothelial function. We hypothesize that IPC will improve physical exercise performance and maximal oxygen consumption. The purpose of the study was to examine the eVect of ischemic preconditioning in leg skeletal muscles on cycling exercise performance in healthy individuals. Fifteen healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
274
5
22

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(319 citation statements)
references
References 24 publications
18
274
5
22
Order By: Relevance
“…Occlusion pressure for the group was between 160-170 mmHg, therefore 220 mmHg ensured the pressure was at least 50 mmHg above systolic blood pressure. This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 55%
See 1 more Smart Citation
“…Occlusion pressure for the group was between 160-170 mmHg, therefore 220 mmHg ensured the pressure was at least 50 mmHg above systolic blood pressure. This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 55%
“…Adenosine may proffer beneficial clinical and exertional effects by acting as a vasodilator (Gustafsson et al 1993), and/or opening potassium (K ATP ) channels, which in turn preserves energy (Pang et al 1997;Cohen et al 2000). This may occur reduced mitochondrial oxygen consumption (Cooper & Brown 2008), although a reduced oxygen consumption for a given submaximal exercise intensity is not uniformly observed (De Groot et al 2010). There is also likely an effect of IP in promoting endothelial nitric oxide biosynthesis (Kimura et al 2007), which appears to maintain vascular function that may be impaired following high intensity exercise (Bailey, Birk, et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the underlying mechanisms are not yet understood. One model of ischemia/reperfusion conditions to be studied in humans can be knee replacement surgery, because in this case, a tourniquet is applied on the knee area to stop the blood flow through the area during the operation (Westman et al, 2007;de Groot et al, 2010). Such orthopedic surgeries are thought to be good models to evaluate the production of antioxidants and for testing antioxidant effects of anesthetic agents.…”
Section: Introductionmentioning
confidence: 99%
“…After that moment the load was increased by 20 W/min until exhaustion. The cadence was maintained between 60 and 80 RPM, and exhaustion was defined as inability of the subject to maintain this cadence 25 .…”
Section: Maximal Cycling Testmentioning
confidence: 99%